2019
DOI: 10.3390/f10010075
|View full text |Cite
|
Sign up to set email alerts
|

Abiotic and Biotic Disturbances Affecting Forest Health in Poland over the Past 30 Years: Impacts of Climate and Forest Management

Abstract: The current nature of forest management in Poland reflects its history and more than 100 years of economic activity affecting forests since independence in 1918. Before that time, different forest management models were used, related to the nature of the Prussian economy in the north of the country, the Russian economy in the central-eastern part, and the Austrian economy in south-eastern Poland. The consequence of these management models, as well as the differing climate zones in which they were used, resulte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 43 publications
1
35
0
2
Order By: Relevance
“…The impact of harmful biotic factors on forest tree species is often assessed by visual estimation of the general health condition of the crown [65,66]. P. cactorum and A. gallica directly destroy the plant root system, and in consequence influence the condition of foliage.…”
Section: Effects Of Stress Factors On Physiological Response Of Plantsmentioning
confidence: 99%
“…The impact of harmful biotic factors on forest tree species is often assessed by visual estimation of the general health condition of the crown [65,66]. P. cactorum and A. gallica directly destroy the plant root system, and in consequence influence the condition of foliage.…”
Section: Effects Of Stress Factors On Physiological Response Of Plantsmentioning
confidence: 99%
“…Choi et al [4] reviewed changes in major forest pests, specifically, insect pests of pine forests in Korea over the last 50 years, and presented the shift in pests from the pine needle gall midge to the pine wilt disease due to changes in the forest structure. Meanwhile, Sierota et al [18] reported on changes in the health of forests and their biological diversity in Poland over the last 30 years, by considering the climate, species composition, impacts of forest pests, forest management, etc. They concluded that forests in Poland are highly diversified but vulnerable to outbreaks of forest pests.…”
Section: Papers In This Issuementioning
confidence: 99%
“…Not only does warming benefit native pests, it may also allow the range expansion and population growth of species never considered as potential pests. Such seems to be the case in Finland with the nun moth (Lymantria monacha L.), one of the most important defoliators of coniferous forests in Europe (Schwenke 1978;Bejer 1988;Sierota et al 2019). Its potential range expansion was discussed already by Vanhanen et al (2007), and recently Fält-Nardman et al (2018a) reported that between 1961 and 2013, the northern distribution limit of the nun moth has shifted ca.…”
Section: Introductionmentioning
confidence: 98%